Pengembangan Media Pembelajaran Interaktif Berbasis Google Sites pada Mata Pelajaran PAI-BP - Fatiha Hasanah; Ali Jusri Pohan; Syamsiah Depalina Siregar; Herawati Siregar (Prodi Pendidikan Keagamaan Islam, 2022)
This research is motivated by the need for innovative and interactive learning media for Islamic Education and Character (PAI-BP), particularly at SMA IT Al-Husnayain Mandailing Natal. PAI-BP learning has previously used conventional methods, thus demonstrating the potential for supplementing learning activities with the use of digital technology. This research aims to develop a google sites-based interactive learning media called “Mabarin PAI” and to determine its validity, practicality, effectiveness, and evaluation. The method used was Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data were collected through interviews, observations, documentation, validation questionnaires for validators and teachers, and student response questionnaires. The results showed that: (1) Media development followed the ADDIE stages and produced an interactive product that met user needs; (2) Validation results from media experts (93,57%), material experts (81%), and teachers (93,33%) indicated a very valid category; (3) Very high practicality, with student scores of 90,05% and teachers of 93,75%; (4) Effectiveness reached 90,37%, in the very good category; and (5) The media has been proven to support digital, independent PAI-BP learning and is suitable for use as an alternative learning resource and PAI-BP learning media.